Laptop selection decision support system according to buyer criteria with the simple additive weighting method - Syani Harahap, Nur Hazimah; Zahraini, Afifah (SHM Publisher, 2021)
Along with the development of increasingly modern times, so that all activities require gadgets, including laptops. However, it is often found among prospective laptop buyers who are still confused in determining a laptop to suit their needs, for that purpose the purpose of this study is to help people who want to buy a laptop when choosing or who are looking for a laptop to get the right one for their needs. To achieve this goal, a decision support system is needed. The Decision Support System that will be used is the SAW (Simple Additive Weighting) method because this method can filter out several existing alternatives and based on predetermined criteria so that later you get the best alternative. By using this SAW method, a matrix normalization process is needed, the weight value of each attribute, and finally a ranking process that will determine the optimal alternative. The results obtained in this study are to be able to provide laptop advice to prospective buyers based on the specifications of the prospective buyers' needs and with a 100% accuracy level based on calculations from the decision support system.